2005
DOI: 10.1007/s10163-004-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic thermophilic bacteria enhance biogas production

Abstract: The enhancing effect of aerobic thermophilic (AT) bacteria on the production of biogas from anaerobically digested sewage sludge (methanogenic sludge) was investigated. Sewage sludge (5%, w/w) was incubated at 65°C with shaking for a few months to prepare the AT seed sludge. AT sludge was prepared by incubation of the AT seed sludge (5%, v/v) and sewage sludge (5%, w/w) at 65°C with shaking. The addition of this AT sludge (1.2% Ϯ 0.5% of total volatile solids) to methanogenic sludge enhanced the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…One could expect two effects of the aerobic pre-treatment: (a) aerobic hydrolytic exo-enzymes secreted by thermophilic aerobic bacteria provide methanogenic metabolites which would benefit methane production (Borowski and Szopa, 2007;Capela et al, 1999;Hasegawa and Katsura, 1999;Miah et al, 2005). (b) aerobic oxidation exhaust the easy-to-degrade component of the starting material (oxidation to CO 2 ) which would otherwise have been used by anaerobic microbes to generate methane (Krzystek et al, 2001).…”
Section: Effect Of Anaerobic Liquid On the Start-up Of Batch Thermophmentioning
confidence: 99%
“…One could expect two effects of the aerobic pre-treatment: (a) aerobic hydrolytic exo-enzymes secreted by thermophilic aerobic bacteria provide methanogenic metabolites which would benefit methane production (Borowski and Szopa, 2007;Capela et al, 1999;Hasegawa and Katsura, 1999;Miah et al, 2005). (b) aerobic oxidation exhaust the easy-to-degrade component of the starting material (oxidation to CO 2 ) which would otherwise have been used by anaerobic microbes to generate methane (Krzystek et al, 2001).…”
Section: Effect Of Anaerobic Liquid On the Start-up Of Batch Thermophmentioning
confidence: 99%
“…The scanning electron microscopy image of the thermophilic bacterium AT07-1 is shown in Figure 2. Some early studies had reported that the bacteria which dissolved sludge effectively were mostly thermophilic bacteria Bacillus [20,31]. On the agar plate, AT07-1 produced semi-transparent, edge-irregular, convex, smooth surface and shallow cleft light gray colonies.…”
Section: Strain Isolation and Identificationmentioning
confidence: 99%
“…Several methods have been suggested for the intensification of biogas productivity, e.g. the facilitation of biomass decomposition by means of various pretreatments, modification of the composition of the microbial community, or conduction of the various anaerobic digestion (AD) phases in separate reactors (Divya, 2015;Miah, 2005;Weiß, 2010).…”
Section: Introductionmentioning
confidence: 99%